2008
DOI: 10.1016/j.chom.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Profilin Is Essential for Host Cell Invasion and TLR11-Dependent Induction of an Interleukin-12 Response

Abstract: Apicomplexan parasites exhibit actin-dependent gliding motility that is essential for migration across biological barriers and host cell invasion. Profilins are key contributors to actin polymerization, and the parasite Toxoplasma gondii possesses a profilin-like protein that is recognized by Toll-like receptor TLR11 in the host innate immune system. Here, we show by conditional disruption of the corresponding gene that T.gondii profilin, while not required for intracellular growth, is indispensable for glidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
322
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(340 citation statements)
references
References 38 publications
(47 reference statements)
8
322
1
9
Order By: Relevance
“…Furthermore, a mouse infection study showed that the suppression of profilin expression attenuated the fungal burden in the kidney, and indicated that the profilin was required for survival in the host's body (Chibana et al,376 K. Ueno, Y. Tamura and H. Chibana unpublished data). Interestingly, the profilin of the parasite pathogen Toxisoplasma is necessary for host cell invasion but not for growth and replication (Plattner et al, 2008). Taken together, the findings described above indicate that the profilin has potential as an antifungal drug target.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a mouse infection study showed that the suppression of profilin expression attenuated the fungal burden in the kidney, and indicated that the profilin was required for survival in the host's body (Chibana et al,376 K. Ueno, Y. Tamura and H. Chibana unpublished data). Interestingly, the profilin of the parasite pathogen Toxisoplasma is necessary for host cell invasion but not for growth and replication (Plattner et al, 2008). Taken together, the findings described above indicate that the profilin has potential as an antifungal drug target.…”
Section: Discussionmentioning
confidence: 89%
“…Several key players have been identified including profilin (PRF), formins (FRMs), and actin depolymerization factor (ADF). Profilin was found to critically contribute to egress, gliding, and host cell invasion (Plattner et al, 2008). In the absence of an ARP2/3 complex, the role of the actin nucleator is carried out by two formins in Plasmodium spp.…”
Section: Actin Dynamicsmentioning
confidence: 99%
“…Gliding motility, more directly myosin ATPase activity, and actin polymerization need to be tightly regulated in a timely and spatial fashion. Several key regulators of actin dynamics including profilin (PRF), formins (FRMs), and actin depolymerization factor (ADF) were found to govern parasite motility (Baum et al, 2008;Daher et al, 2010;Mehta and Sibley, 2011;Plattner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The obvious advantage of this strategy is that hypothetical genes that might otherwise be neglected in targeted approaches will be identified with equal probability. The Tet-inducible transactivator system is currently the most robust method to generate conditional mutants for essential genes in a targeted approach and appears to be especially well suited for the characterisation of factors involved in invasion and apicoplast biology (Meissner et al 2002, Mital et al 2005, Huynh & Carruthers 2006, Mazumdar et al 2006, Kessler et al 2008, Plattner et al 2008) whereas employment of the system for other essential GOIs might result only in weak phenotypes (Fleige et al 2008) or might not be possible at all (unpublished observations). A major advantage of the Tet-inducible system is that virtually any GOI can be regulated whereas regulation at the protein level using ddFKBP might not work for proteins targeted to the secretory system (Herm-Gotz et al 2007, and unpublished observations).…”
Section: Molecular Tools For Identification and Characterisation Of Ementioning
confidence: 99%